2003
DOI: 10.1155/s1110865703211136
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Suppression in Ultrasonic Images Based on Undecimated Wavelets

Abstract: An original method to denoise ultrasonic images affected by speckle is presented. Speckle is modeled as a signal-dependent noise corrupting the image. Noise reduction is approached as a Wiener-like filtering performed in a shift-invariant wavelet domain by means of an adaptive rescaling of the coefficients of an undecimated octave decomposition. The scaling factor of each coefficient is calculated from local statistics of the degraded image, the parameters of the noise model, and the wavelet filters. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…In [20], based on the experimental estimation of the mean versus the standard deviation in Log-compressed images, Loupas et al have shown that c = 0.5 model fits better to data than the multiplicative model or the Rayleigh model. Since, this model has been used successfully in many studies [2,11,16,29]. Clearly, this model is relevant since it is confirmed that the speckle is higher in regions of high intensities versus regions of low intensities [16,26].…”
Section: Bayesian Nl-meansmentioning
confidence: 92%
“…In [20], based on the experimental estimation of the mean versus the standard deviation in Log-compressed images, Loupas et al have shown that c = 0.5 model fits better to data than the multiplicative model or the Rayleigh model. Since, this model has been used successfully in many studies [2,11,16,29]. Clearly, this model is relevant since it is confirmed that the speckle is higher in regions of high intensities versus regions of low intensities [16,26].…”
Section: Bayesian Nl-meansmentioning
confidence: 92%
“…Recent studies into US images also demonstrate that the distribution of noise is satisfactorily approximated through a gamma distribution [65] or a Fisher-Tippett distribution [66]. Therefore, we adopted Loupas noise model [67], which has been successfully used in many studies [68]- [70], because it is more flexible and less restrictive than the usual Radio Frequency model; furthermore, it can capture reliable image statistics since factor γ depends on the US devices and the additional processing related to image formation. Furthermore, Loupas et al demonstrated that, with γ = 0.5, the model fits the data better than multiplicative or Rayleigh models.…”
Section: Nl(u)(mentioning
confidence: 99%
“…Whenever f · u w, as it happens for SAR speckle, it stems that γ eq (f ) → 1 − . In practice, the left-hand side of (2), i.e., (1) with γ = 1, is taken as a noise model suitable for ultrasonic images [10].…”
Section: Signal-dependent Noise Modelingmentioning
confidence: 99%